IDENTIFIKASI DENPASAR SEBAGAI KOTA WISATA BUDAYA DITINJAU DARI DELAPAN ELEMEN PERANCANGAN KOTA - Widiantara, Gusti Agung Bagus (Jurnal Manajemen Pelayanan Hotel, 2020)
This research coverage is Jalan Gajah Mada Denpasar. It is chosen because it is the right location to observe the eight elements of urban design that have long been built. This area also has many functions, namely the Heritage area, the trade center (CBD) and as the center of Denpasar City. This road is very identical with the crowd, because very crowded with the activities of the people of Denpasar City. The purposes of this study were to determine the eight elements of the design of the city of Denpasar as a city of cultural tourism, the potential and supporting elements owned by Denpasar as a city of cultural tourism. The Eight elements of the city design are: Land Use, Building Form and Massing, Circulation and Parking, Open Space, Pedestrian area, signage activity support and Conservation. The data analysis technique used in this study was Qualitative Descriptive Method. Based on data analysis on each element of urban planning, it can be concluded that Denpasar City is worthy of being called as a cultural tourism city, because there are elements of Balinese culture that are still well. Keywords: Denpasar City, elements of urban design, cultural tourism